2024
DOI: 10.1177/13524585241228423
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal enlargement of choroid plexus is associated with chronic lesion expansion and neurodegeneration in RRMS patients

Samuel Klistorner,
Michael H Barnett,
Chenyu Wang
et al.

Abstract: Background and Objective: We explored dynamic changes in the choroid plexus (CP) in patients with relapsing-remitting multiple sclerosis (RRMS) and assessed its relationship with chronic lesion expansion and atrophy in various brain compartments. Methods: Fifty-seven RRMS patients were annually assessed for a minimum of 48 months with 3D FLAIR, pre- and post-contrast 3D T1 and diffusion-weighted magnetic resonance imaging (MRI). The CP was manually segmented at baseline and last follow-up. Results: The volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Although some studies provided evidence favoring an association between CP/TIV ratio and neurodegenerative changes, such as cortical thinning or deep GM atrophy in MS, other studies suggested that CP inflammation may not be the primary cause of neurodegeneration [19,33,39].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although some studies provided evidence favoring an association between CP/TIV ratio and neurodegenerative changes, such as cortical thinning or deep GM atrophy in MS, other studies suggested that CP inflammation may not be the primary cause of neurodegeneration [19,33,39].…”
Section: Discussionmentioning
confidence: 99%
“…According to Klistorner and co-workers, normalized CPV was robustly associated with deep gray matter (GM) volume loss (as measured by ventricular enlargement) and only slightly with cortical or whole brain atrophy. Furthermore, the progressive plexus enlargement was associated with the volume of chronic lesion expansion, but not with the number or volume of new lesion load [31,33]. These associations imply that the CP could be involved in (the beginning or sustaining) the low-grade inflammatory process at the edges of chronic periventricular MS lesions [20,[33][34][35].…”
Section: Cp Enlargement As a Biomarker Of Neurodegenerationmentioning
confidence: 97%
See 3 more Smart Citations